Big Book in Early Reading Learning in Lower-Class Elementary School - Harsiwi, Nova Estu; Yunarni, Yunarni (Jurnal Pendidikan Anak, 2021)
Problems at the initial reading stage must be overcome so that students do not have difficulty in reading. Efforts are made to overcome the problem of reading at the beginning of grade I elementary school students by using big book learning media. This research aims to know: (1) the use of the big book in reading learning begins. (2) student learning outcomes by using big books in initial reading activities in Karangpatihan 3 Elementary School. This research is qualitative research with a type of descriptive research. The study subjects were students of class I SDN 3 Karangpatihan, totaling 23 people. Data collection techniques in the form of tests and observations. The results showed an average score at the pre-tests of 75.43 and post-tests 80.65. Post-test results showed 13 students in the good category at 56.52% and 10 students in the good category with a percentage of 43.48%. Thus, it can be concluded that the use of Big Book media positively influences the ability to read the beginning in 1st-grade students in Karangpatihan 3 Elementary School.